Mapping the field - Mariekie Burger (Communicare)
Despite a vast array of HIV/AIDS prevention communication initiatives in South Africa, recent research pointed out that the general public’s knowledge level about HIV/AIDS has decreased and that risky behaviour associated with the spread of the virus, is on the increase. This means that even though some successes with HIV/AIDS prevention communication have been achieved, new innovative ways of communicating about the epidemic urgently needs to be investigated. In search for a new direction, this article maps four forms of HIV/AIDS prevention communication in the country. Instead of continuing on the trajectory of exploring project-based campaigns that are initiated ‘from the outside’ (such as projects formulated by donor institutions), this article suggests that community-initiated HIV/AIDS prevention communication initiatives might suggest a new direction to supplement existing communication on the epidemic.